EPIDEMICS IN KYIV COVERED IN THE NEWSPAPER PERIODICALS OF THE CITY OF THE LATE 19TH – EARLY 20TH CENTURIES - Анна ГЕДЬО; Марк МІЛЮТІН (Cхід)
The article examines the coverage of the sanitary and epidemiological situation in the city in the late 19th – early 20th centuries in the Kyiv newspapers “Kievlyanin”, “Kievskie Vesti”, “Kievskaya Mysl”, “Yuzhnaya Kopeyka”. The processing of newspaper materials made it possible to identify problematic areas of work of the city authorities in the sanitary and communal spheres, namely inadequate control over observance of health standards in urban markets, failure to solve the problem of natural dumps and homeless people, illegal alcohol sales, lack of timely repair of roads, construction of water supply and sewerage. These factors were the main causes of epidemics of typhus, measles, tuberculosis, smallpox, cholera. Analysis of statistics on the pages of periodicals allows tracing the number of people affected by epidemics, identifying typical diseases for each district of the city, caused by their geographical location, population, location of facilities such as prisons, bazaars, cemeteries, hospitals.